Adding Rows in Main e-Abacus Diagrams - Mahmood, Ammar S.; Khaleel, Jwan K. (Iraqi Journal of Science, 2024)
In the past years, there was an attempt to add one column to the e-abacus diagram, then another work followed by other researchers by adding several columns to the same diagram. At that time, a question remained, is it possible to add a row and later several rows on the same diagram? Or is this not an easy thing except under certain conditions? In this research, we will know when we can take these steps.